Dietary Photoprotective Compounds Ameliorate UV Tolerance in Shrimp (Pleoticus muelleri) through Induction of Antioxidant Activity - Marcoval, Maria Alejandra (2017)
The aim of this study was to determine the effects of ultraviolet radiation (UVR) on bioaccumulation of UV-absorbing compounds acquired through the diet, in larvae and postlarvae of Pleoticus muelleri, and to assess tissue antioxidant activity, survival, and development. Mysis stage I were exposed to two artificial radiation treatments: M-PAR (photosynthetically active radiation, range=400-700nm) and M-PAR+UVR (280-700nm). The experimental larvae received a mixed dietary treatment of Artemia persimilis and the microalga Pavlova lutheri, reared under two radiation regimes: PAR (D-PAR) and PAR+UVR (D-PAR+UVR). Shrimp from all treatments reached 8 d postlarval stage (PL8), except those under M-PAR+UVR treatment fed the D-PAR-cultured algae, which had 0% survival. Larvae in M-PAR+UVR and M-PAR treatments fed with D-PAR+UVR diet presented the highest survival rates (70 and 75%, respectively), with 37 and 41% increase in PL size. UV-absorbing compounds were detected in microalgae and PL subject to PAR+UVR treatments. Antioxidant activity, quantified by measuring the free-radical 1,1-diphenyl-2-picrylhydrazyl in homogenates of PL8, decayed drastically under radiation treatment M-PAR+UVR fed with algae of the D-PAR+UVR treatment. It is concluded that the bioaccumulation of UV-absorbing compounds and the highest antioxidant activity in PL could improve the biochemical and photophysiological responses of shrimp under UVR stress.